Efficacy of 25% dextrose gel in reducing procedural pain in preterm infants: a prospective observational study - Kumar, Krishnappa S.; Rao, Sameera S.; Krishnappa, Alok Kumar Mandya; Sharaschandra, Spoorthi; Harish , Sahana (International Journal of Contemporary Pediatrics, 2025)
Background: Preterm infants in neonatal intensive care units (NICUs) undergo frequent painful procedures, increasing their risk for adverse neurodevelopmental outcomes. Non-pharmacologic interventions are sought for safe, effective pain management. We evaluated the efficacy of 25% dextrose gel (Nanodex, Analeptik Biologicals) for procedural pain relief in preterm neonates. Methods: This prospective observational study enrolled 53 preterm infants over 12 months. 25% dextrose gel (Nanodex, Analeptik Biologicals) was administered buccally at 0.5 ml/kg, 2 minutes before procedures including venepuncture, intubation, heel prick, nasogastric/orogastric tube insertions, and retinopathy of prematurity (ROP) screening. Historical data was used as control group. Pain was assessed using the premature infant pain profile (PIPP) score. Results: The mean PIPP score across all procedures was significantly lower post-25% dextrose gel (mean: 6.9±1.9) compared to historical reference scores (mean: 11.2±2.1, p<0.001). The greatest reduction was observed during ROP screening. No adverse events were recorded. Conclusions: 25% dextrose gel is a safe and effective intervention for procedural pain management in preterm infants. Its routine use in NICU protocols should be considered.